Biologisation(s) Les usages sociaux de l'argument biologique en santé - Thizy, Laurine; Vincent, Justine; Sinem, Gunes; Nihan Balci, Irem (Sociétés, Espaces, Temps, 2023)
This book deals with the phenomena of "biologisation" in the field of health, i.e. all situations where biological causality prevails in establishing the determinants of human health, to the detriment of other interpretations. It is based on ethnographic field studies carried out with caregivers and patients by researchers in the humanities and social sciences, and on socio-historical discussions to clarify the proposed concept. This collective work extends the existing work on biologisation by considering its "practical" dimension: which actors in the field of health mobilise these biologising arguments? In which contexts? To what ends, and with what effects?